Association of Hypokalemia Incidence and Better Treatment Response in NSCLC Patients: A Meta-Analysis and Systematic Review on Anti-EGFR Targeted Therapy Clinical Trials - Zhou, Jiawei; Bai, Jianling; Yue, Yuanping; Chen, Xin; Lange, Theis; You, Dongfang; Zhao, Yang (Frontiers in Oncology, 2022)
Background: This meta-analysis was designed to explore the relationship between serum potassium level and treatment effect of epidermal growth factor receptor (EGFR) antagonist in advanced non-small cell lung cancer (aNSCLC). Methods: We searched phase II/III prospective clinical trials treated with EGFR antagonists for aNSCLC patients. The objective response rate (ORR) and/or disease control rate (DCR) and the incidence of hypokalemia of high grade (equal to or greater than grade 3) were summarized from all eligible trials. Heterogeneity, which evaluated by Cochran's Q-test and the I2 statistics, was used to determine whether random effect model or fixed effect model used to calculate pooled proportions. Subgroup analysis was performed on different interventions, line types, phases, and drug numbers. Results: From 666 potentially relevant articles, 36 clinical trials with total 9,761 participants were included in this meta-analysis. The pooled ORR was 16.25% (95%CI: 12.45%-21.19%) when the incidence of hypokalemia was 0-5%, and it increased to 34.58% (95%CI: 24.09%-45.07%) when the incidence of hypokalemia was greater than 5%. The pooled DCR were 56.03% (95%CI: 45.03%-67.03%) and 64.38% (95%CI: 48.60%-80.17%) when the incidence of hypokalemia was 0-5% and greater than 5%, respectively. Subgroup analysis was consistent with the results of whole population except for not first-line treatment, which may confound by malnutrition of poor life quality in long-time survival. Conclusion: Efficacy of anti-EGFR target therapy was positively associated with hypokalemia incidence rate. Treatment effect on different serum potassium strata needs to be considered in future clinical trials with target therapy.